Grain maceration of Chenopodium quinoa Willd: effect of time and temperature (Research, Society and Development, 2020)
Quinoa has aroused worldwide interest for its high nutritional value, especially in relation to protein content. Therefore, the objective of this study was to evaluate the effect of time and temperature on the maceration of quinoa in order to obtain greater submersion with less loss of grain proteins. To characterize the quinoa grains, the material was crushed and subjected to moisture, protein, lipid and ash analysis. To evaluate time and temperature, the grains were macerated at three different temperatures (5 ºC, 25 ºC and 45 ºC) in a 1:2 ratio (quinoa: water) for 48 hours. Samples of the maceration water were subjected to analysis of hydrogen potential, protein determination, acidity and water absorption. The experiment was carried out in a Subdivided Plot Design with the temperature in the plot (3 levels - 5 °C, 25 °C and 45 °C) with three repetitions and the maceration time in the subplot (9 levels - 9 times). All analysis were performed in duplicate. Regarding the results obtained, quinoa can be considered a food with a high protein content (14.35%). Note that the migration of proteins to the maceration water is greater at a temperature of 45 °C. The results for the behavior of pH and acidity show that there was fermentation at temperatures of 25 ºC and 45 °C. The mass gain is independent of the temperature and reached a maximum waterlogging point around 16 hours. So it is recommended to macerate the quinoa at a temperature of 5 °C for 16 hours.